Full-scale bioremediation of diesel-polluted soil in an Arctic landfarm. (1st July 2021) - Johnsen, Anders R.; Boe, Uffe S.; Henriksen, Peter; Malmquist, Linus M.V.; Christensen, Jan H.
Abstract: A full-scale, experimental landfarm was tested for the capacity to biodegrade oil-polluted soil under high-Arctic tundra conditions in northeast Greenland at the military outpost 9117 Station Mestersvig. Soil contaminated with Arctic diesel was transferred to the landfarm in August 2012 followed by yearly addition of fertilizer and plowing and irrigation to optimize microbial diesel biodegradation. Biodegradation was determined from changes in total petroleum hydrocarbons (TPH), enumeration of specific subpopulations of oil-degrading microorganisms (MPN), and changes in selected classes of alkylated isomers and isomer ratios. Sixty-four percent of the diesel was removed in the landfarm within the first year, but a recalcitrant fraction (18%) remained after five years. n -alkanes and naphthalenes were biodegraded as demonstrated by changing isomer ratios. Dibenzothiophenes and phenanthrenes showed almost constant isomer ratios indicating that their removal was mostly abiotic. Oil-degrading microorganisms were present for the major components of diesel ( n -alkanes, alkylbenzenes and alkylnaphthalenes). The degraders showed very large population increases in the landfarm with a peak population of 1.2 × 10 9 cells g −1 of total diesel degraders. Some diesel compounds such as cycloalkanes, hydroxy-PAHs and sulfur-heterocycles had very few or no specific degraders, these compounds may consequently be degraded only by slow co-metabolic processes or not at all. Graphical abstract: Image 1 Highlights: Diesel-degrading microorganisms were extremely enriched in the landfarm. Some minor diesel compounds (cycloalkanes, hydroxy-PAHs and sulfur-heterocycles) had no detectable degraders. Eighty-two percent of the diesel was removed in the landfarm but a recalcitrant fraction (18%) remained after five years. Abstract : Diesel polluted soil in an Arctic landfarm developed a high potential for degradation of n -alkanes and various one-, two- and three-ring aromatics. Sixty-four percent of the diesel was removed within the first year, but a recalcitrant fraction (18%) remained after five years.